FAKTOR-FAKTOR YANG MEMPENGARUHI KUALITAS LAPORAN KEUANGAN PEMERINTAH DAERAH PROVINSI SULAWESI SELATAN - Nurafni Baturante; Jeni Kamase; Fadliah Nasaruddin (SEIKO : Journal of Management & Business, 2018)
Abstract The objectives of this study are to determain and obtain empirical evidence related the effect of human resource competence, the application of Government Accounting Standard, the application of Government Internal Control System, the utilization of technology, the review of financial report and bureaucratic culture on the quality of financial report in Government of South Sulawesi. This research was conducted on entire financial administration entity accounting official local government unit (OPD) of Government of South Sulawes,using primary data obtained from questionnaires distributed to respondent. Analysis of data using regression analysis linear multiple by SPSS Program. Partial test result show competence of human resources and the utilization of information technology have a significant positive effect on the quality of quality of financial report, while the application of SPIP, the application of SAP, the review of the Financial Statements and Bureaucratic Culture has no effect on the quality quality of financial report. Keywords: Competence, implementation of SPIP and SAP,  information technology, financial report review, bureaucratic culture and quality of financial report